Implementing Guided-Discovery Grammar Learning - Achoy Solano, Daniela (2020)
This inquiry explores the implementation of guided discovery as a means to promote analyzing and reasoning skills in the study of grammar in the English as a Foreign Language (EFL) class. A grammar guided discovery learning-based action plan was analyzed based. This study acknowledges the need to develop analytical and reasoning skills when learning grammar and highlights the relevance of reflecting upon current teaching practices to attain effective grammar learning